Political Islam and Constitutional Change in Contemporary Indonesia - Mukrimin Mukrimin (Al-Mizan (e-Journal), 2023)
This article examines how Islam and Indonesia's constitution interact. It shows Islam's complicated relationship with politics. It intends to analyze and investigate how religious beliefs and values influence political discourse and decision-making in various circumstances. It is hoped to shed new light on this critical and often controversial topic and help us comprehend the forces that influence our world by exploring Islam in modern political debates and conversations. Therefore, this article discusses the challenges between religious freedom and democracy in Indonesia. It also presents a detailed and analytical examination of the complicated and multi-faceted question of the future of Islam and constitutionalism in Indonesia, a country with a rich history and diverse culture. The finding of this study shows that political Islam and constitutional ideas affect Indonesia's political and social situation. Then this article seeks to illuminate Indonesia's future difficulties, possibilities, and outcomes through critical study.